Effect of exercise-cognition integrated training for enhancement (ExCITE) programme on gait parameters in young healthy adults - Ho, Shu Yu (2018)
Walking is an important functional activity which requires efficient cerebellar coordination to perform activities of daily living. It is suggested that enhanced cerebellar connectivity could be induced by sensorimotor training. The objective of this study was to study the effects of 6-weeks Exercise-Cognition Integrated Training for Enhancement (ExCITE) training program on the gait characteristics (gait speed and step length), in young adults compared to control group. It was hypothesized that the ExCITE program would lead to improvements in gait parameters in the whole-body group versus control group. A total of 8 adults (2 males, 6 females; M age = 24 years, SD age = 2.673) were tested individually and randomly assigned to either the ExCITE: whole-body (WB) (n = 4) or control group (n = 4). Gait was investigated at participant’s usual, comfortable speed using an optical gait measurement system along a 10-metres walkway at three-time points (Baseline – Pre-session, Mid – 6th Session, Post – 11th Session). A mixed design was used with statistical significance set at alpha = 0.05. Results showed no significant difference in gait speed and step length between participants in the Whole-Body and Control groups. Similarly, no significant difference in gait speed and step length of participants within the Whole-Body and Control group across the three-time points. In conclusion, findings suggest that 6 weeks intervention of ExCITE Program training is unlikely to improve step length in young healthy adults.